Understanding the female adolescent singing voice : pedagogical perspectives and practical strategies for choral conductors - Oosthuizen, Adriaan Desmond (Stellenbosch : Stellenbosch University, 2026)
Thesis ( MMus)--Stellenbosch University, 2026.